2013
DOI: 10.1186/2049-1891-4-36
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of endogenous protein and amino acid ileal losses in weaned piglets by regression analysis using diets with graded levels of casein

Abstract: BackgroundMany studies have investigated endogenous loss of proteins and amino acids (AAs) at the ileal level in growing pigs. However, only a few studies have researched this subject in piglets. Knowledge regarding AA ileal digestibility in piglets would be helpful during the formulation of diets for weaning piglets, rather than just using coefficients obtained in growing pigs. Therefore, in this study, we sought to estimate endogenous protein and AA ileal losses in piglets. Furthermore, apparent and true ile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 24 publications
3
5
0
2
Order By: Relevance
“…Reported protein AID values for casein range from 81% to 89% (Walker et al., ; Mariscal‐Landín and Reis de Souza, ; Mariscal‐Landín et al., ; Cervantes‐Pahm and Stein, ; Reis de Souza et al., ), consistent with the values observed in the present study. The average indispensable AA AID of casein reported in the literature vary from 85.8% to 91.2%, while dispensable AA AID values range from 80.2% to 88.1% (Walker et al., ; Mariscal‐Landín and Reis de Souza, ; Mariscal‐Landín et al., ; Cervantes‐Pahm and Stein, ).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Reported protein AID values for casein range from 81% to 89% (Walker et al., ; Mariscal‐Landín and Reis de Souza, ; Mariscal‐Landín et al., ; Cervantes‐Pahm and Stein, ; Reis de Souza et al., ), consistent with the values observed in the present study. The average indispensable AA AID of casein reported in the literature vary from 85.8% to 91.2%, while dispensable AA AID values range from 80.2% to 88.1% (Walker et al., ; Mariscal‐Landín and Reis de Souza, ; Mariscal‐Landín et al., ; Cervantes‐Pahm and Stein, ).…”
Section: Discussionsupporting
confidence: 91%
“…The protein and AA SID of casein observed in this study was similar to other studies with weanling pigs (Walker et al, 1986) and slightly lower than values reported in older and heavier piglets by Cervantes-Pahm and Stein (2010). Casein CP SID was similar to true ileal digestibility values estimated by regression for piglets of the same age (Reis de Souza et al, 2013). Some AA SID values, mainly those of indispensable AAs, were slightly lower than the AA true ileal digestibility values reported by these authors.…”
Section: Standardized Ileal Digestibility Of Raw Materialssupporting
confidence: 86%
“…Thus, extrapolation of IAA end from a dietary CP level of 109.1 g/kg DM to zero CP intake may be associated with some uncertainties as also indicated by the large standard error in the present study. On the other hand, all estimates of IAA end obtained in the present study were significantly different from zero, which is in agreement with the results of several other studies, where dietary CP levels of approximately 100 g/kg assay diet resulted in significant estimates of IAA end associated with large standard errors [ 3 , 13 , 34 , 36 , 41 , 42 ]. However, at smaller dietary CP below 50 g/kg, total (IAA end + feed specific) endogenous losses may increase in a nonlinear manner with increasing dietary inclusion level of the assay feed ingredient [ 43 ].…”
Section: Discussionsupporting
confidence: 93%
“…The γ-kafirins have a more effect on the digestibility of protein bodies than other kafirins as they have spatial stability due to their disulphide bonds ( Crevieu-Gabriel, 1999 ). Therefore, the higher content of γ-kafirins in LK sorghum could cause a more loss of the endogenous proteins in response to its lower digestibility, mainly because endogenous proteins are rich in threonine, proline, serine, and glycine ( Mariscal-Landín and Reis de Souza, 2006 , Ravindran, 2016 , Reis de Souza et al., 2013 ). This might explain the comparatively low digestibility of threonine and serine in LK sorghum, and the difference observed in feed efficiency among pigs that were fed diets with low-tannin sorghums and those that were fed a corn diet ( Marques et al., 2007 ).…”
Section: Discussionmentioning
confidence: 99%